2013
DOI: 10.1017/s1368980013000268
|View full text |Cite
|
Sign up to set email alerts
|

Eating location is associated with the nutritional quality of the diet in Norwegian adults

Abstract: Objective: To study the association between dinner eating location and the nutritional quality of the specific dinner meal and the whole-day dietary intake and to compare the diets of those consuming $25 % of energy out of home and at school/work (SOH; substantial out-of-home eaters) with those consuming ,25 % of energy out (NSOH; non-substantial out-of-home eaters). Design: Cross-sectional dietary survey using two non-consecutive 24 h recalls. Recorded eating locations were at home, other private households, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 27 publications
3
36
2
2
Order By: Relevance
“…In a study of 226 US adults, Liu et al [ 27 ] found that eating at work was associated with greater odds of consuming both healthy and unhealthy snacks. We previously studied differences in the composition of dinner meals eaten in different locations [ 14 ] and found that at-home dinners were generally healthier than dinners eaten in other eating locations, with the exception of dinners eaten at work. No differences were observed between dinners eaten at work and dinners eaten at home, but the data were limited, as very few dinners had been consumed at work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 226 US adults, Liu et al [ 27 ] found that eating at work was associated with greater odds of consuming both healthy and unhealthy snacks. We previously studied differences in the composition of dinner meals eaten in different locations [ 14 ] and found that at-home dinners were generally healthier than dinners eaten in other eating locations, with the exception of dinners eaten at work. No differences were observed between dinners eaten at work and dinners eaten at home, but the data were limited, as very few dinners had been consumed at work.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low participation rate of 37% limits the generalizability of the results. The proportion of participants with a college/university education was higher than in the general population [ 14 ]. Because more highly educated individuals are more likely to consume healthier diets than those with less education [ 28 , 29 ], we may assume that more unhealthy snacks might have been reported if the participation rate had been higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, individuals who did not report any OH dietary intake or reported consuming on average less than 25 % of their daily energy intake at eating out places were regarded as not substantial OH eaters. These definitions have been used in previous publications ( 11 , 20 , 21 ) .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Outros estudos já evidenciaram que a alimentação dentro de casa faz com que as escolhas sejam menos calóricas e incluam mais hortaliças e frutas. Segundo Myhre et al (2014), a alimentação fora de casa tende a ter menos consumo de hortaliças, o suco e a água são substituídos por refrigerantes e as frutas na sobremesa, por doce. No que tange ao horário de consumo das frutas e das hortaliças, 26,44% dos registros do consumo das frutas ocorreram no lanche da manhã; 18,25%, no almoço; e 26,23%, no lanche da tarde, ao passo que o consumo de hortaliças foi, predominantemente, nos horários do almoço e jantar.…”
Section: Consumo De Frutas E De Hortaliças Segundo Local Horário E Munclassified